Wasaya Nafiʿah li-Ightinami Shahri al-Khayrat Sermon by Sheikh Faysal al-Ghazzawi: Shift in Meaning in the Indonesian Translation: Khutbah Wasaya Nafi'ah li-Ightinami Shahri al-Khayrat li al-Shaykh Faysal al-Ghazzawi: Tahawwul al-Ma'na fi al-Tarjamah al-Indunisiyyah - Baiq Hikmatussofa (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
The translation of Arabic religious sermons into Indonesian often involves shifts in meaning and structure due to differences in linguistic, grammatical, and cultural systems between the two languages. This study examines meaning shifts in the Indonesian translation of the sermon Waṣāyā Nāfiʿah li-Ightinām Shahri al-Khayrāt by Sheikh Fayṣal Al-Ghazzāwī, translated by Iqbal Kadir. Using a qualitative descriptive approach, the research compares the Arabic source text and its Indonesian target text to identify types of translation shifts and to evaluate their communicative effect. Data are collected through close reading and note-taking of parallel sermon texts from online sources, then analyzed contrastively. The findings reveal the occurrence of structure shifts, class shifts, unit shifts, and intra-system shifts that arise from differences in grammatical systems, lexical choices, and idiomatic tendencies between Arabic and Indonesian. These shifts are closely related to meaning-based translation strategies that balance form-focused rendering in doctrinal formulas with more flexible rendering in persuasive and rhetorical passages. The study concludes that such shifts are not translation errors but deliberate linguistic and communicative strategies to preserve the clarity, spiritual impact, and cultural relevance of religious messages for Indonesian readers. يُعَدُّ نقلُ الخطب الدينية من اللغة العربية إلى اللغة الإندونيسية عمليةً كثيرًا ما تنطوي على تحوّلات في المعنى والبنية، نتيجةً لاختلاف الأنظمة اللغوية والنحوية والثقافية بين اللغتين. تهدف هذه الدراسة إلى بحث التحوّلات الدلالية في الترجمة الإندونيسية لخطبة «وصايا نافعة لاغتنام شهر الخيرات» للشيخ فيصل الغزاوي، التي ترجمها إقبال قادر. واعتمدت الدراسة منهجًا وصفيًّا نوعيًّا من خلال مقارنة النص العربي المصدر بالنص الإندونيسي الهدف؛ بهدف تحديد أنواع التحوّلات الترجمية وتقويم أثرها التواصلي. جُمعت البيانات عن طريق القراءة المتأنية وتدوين الملاحظات على النصوص المتوازية للخطبة المتاحة عبر المصادر الإلكترونية، ثم حُلِّلت تحليلاً تقابليًّا. وأظهرت النتائج وجود تحوّلات بنيوية، وتحولات في الفئة النحوية، وتحولات في الوحدة اللغوية، وتحولات داخل النظام، وهي تحوّلات تنشأ عن الاختلافات في الأنظمة النحوية، والاختيارات المعجمية، والميول الاصطلاحية بين العربية والإندونيسية. وترتبط هذه التحوّلات ارتباطًا وثيقًا باستراتيجيات ترجمة قائمة على المعنى، تُوازن بين المحافظة على الصياغة الأصلية في العبارات العقدية والدينية الثابتة، وبين قدر أكبر من المرونة في المقاطع الإقناعية والبلاغية. وتخلص الدراسة إلى أن هذه التحوّلات لا تمثّل أخطاءً في الترجمة، بل تُعدّ استراتيجيات لغوية وتواصلية مقصودة تهدف إلى الحفاظ على وضوح الرسائل الدينية، وتأثيرها الروحي، وملاءمتها الثقافية لدى القارئ الإندونيسي. Penerjemahan khutbah keagamaan dari bahasa Arab ke bahasa Indonesia sering kali menimbulkan pergeseran makna dan struktur akibat perbedaan sistem linguistik, gramatikal, dan budaya antara kedua bahasa tersebut. Penelitian ini mengkaji pergeseran makna dalam terjemahan khutbah Waṣāyā Nāfiʿah li-Ightinām Shahri al-Khayrāt karya Syaikh Fayṣal Al-Ghazzāwī yang diterjemahkan ke dalam bahasa Indonesia oleh Iqbal Kadir. Dengan pendekatan kualitatif deskriptif, penelitian ini membandingkan teks sumber berbahasa Arab dan teks sasaran berbahasa Indonesia untuk mengidentifikasi jenis-jenis pergeseran terjemahan serta menilai dampak komunikatifnya. Data dikumpulkan melalui pembacaan cermat dan pencatatan terhadap teks khutbah paralel, kemudian dianalisis secara kontrastif. Hasil penelitian menunjukkan adanya structure shift, class shift, unit shift, dan intra-system shift yang muncul akibat perbedaan sistem gramatikal, pilihan leksikal, dan kecenderungan idiomatik antara bahasa Arab dan bahasa Indonesia. Pergeseran-pergeseran tersebut berkaitan erat dengan strategi penerjemahan yang berorientasi makna, yang memadukan kecenderungan mempertahankan bentuk pada bagian-bagian doktrinal dengan keluwesan pada bagian persuasif dan retoris. Penelitian ini menyimpulkan bahwa pergeseran tersebut bukan merupakan kesalahan penerjemahan, melainkan strategi linguistik dan komunikatif untuk menjaga kejelasan, daya spiritual, dan relevansi budaya pesan-pesan keagamaan bagi pembaca Indonesia.